Perception of Directionality in Translation Among Students - Pietryga, Marcelina (Acta Neophilologica, 2022)
The present study, in the form of a questionnaire, aims to analyze students’ subjective perceptions of directionality in translation. Additionally, it places a particular emphasis on aspects which are perceived as difficult in each direction. Although for most students, L2 translation is more cognitively demanding, and they prefer to translate into L1, such preferences may change as the result of the amount of translation training. Students with a longer span in translation training frequently encounter more problems in L1 translation and may not have any preferred direction of translation. Nevertheless, the importance of practicing translating into L2 has been emphasized in many aspects, such as expanding L2 competence or translation market demand. Additionally, it is also the preferred language of translation for some students.Vocabulary and terminology have been described as the most problematic as regards both directions of translation. Other aspects which pose many problems and require some training are both L1 and L2 grammar as well as punctuation.